Prevalence of COVID-19 in Iran: results of the first survey of the Iranian COVID-19 Serological Surveillance programme. (November 2021) - Khalagi, Kazem; Gharibzadeh, Safoora; Khalili, Davood; Mansournia, Mohammad Ali; Mirab Samiee, Siamak; Aghamohamadi, Saeide; Mir-Mohammad-Ali Roodaki, Maryam; Hashemi, Seyed Mahmoud; Tayeri, Katayoun; Namdari Tabar, Hengameh; Azadmanesh, Kayhan; Tabrizi, Jafar Sadegh; et al.
Abstract: Objectives: This study aims to estimate the prevalence of coronavirus disease 2019 (COVID-19) in the general population of Iran. Methods: The target population was all Iranian people aged 6 years and older in the country. A stratified random sampling design was used to select 28 314 people from among the individuals registered in the electronic health record systems used in primary health care in Iran. Venous blood was taken from each participant and tested for the IgG antibody against COVID-19. The prevalence of COVID-19 was estimated at provincial and national levels after adjusting for the measurement error of the laboratory test, non-response bias and sampling design. Results: Of the 28 314 Iranians selected, 11 256 (39.75%) participated in the study. Of these, 5406 (48.0%) were male and 6851 (60.9%) lived in urban areas. The mean (standard deviation) participant age was 35.89 (18.61) years. The adjusted prevalence of COVID-19 until 20 August 2020 was estimated as 14.2% (95% uncertainty interval 13.3%–15.2%), which was equal to 11 958 346 (95% CI 11 211 011–12 746 776) individuals. The adjusted prevalences of infection were 14.6%, 13.8%, 16.6%, 11.7% and 19.4% among men, women, urban population, rural population and individuals aged 60 years or more, respectively. Ardabil, Golestan and Khuzestan provinces had the highest prevalence and Alborz, Hormozgan and Kerman provinces had the lowest. Conclusions: Based on the study results, a large proportion of the Iranian population had not yet been infected by COVID-19. The observance of hygienic principles and social restrictions should therefore continue until the majority of the population has been vaccinated.